Pengaruh Islamic Law System Terhadap Hukum Ekonomi Indonesia - Tutik Nurul Janah (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
Islamic Law System is generally applied in Islamic countries. An Islamic state is a country that uses Islamic law as the formal law of the state. Indonesia is a country with a dominant legal system using the Civil Law System. However, despite the dominant use of the Civil Law System, the Islamic Law System is also quite influential in Indonesia, especially in Privat law and economic law. The influence of the Islamic Law System in Indonesian economic law can be seen from the passing of the Law on Sharia Banking and other Legislation relating to Islamic economics. The dynamics of the speed of the needs of economic actors for legislation makes economic law the most dynamic field of law among other fields of legal study. Nevertheless, the legal norms must not be in conflict with human rights and humanity in order to achieve social justice for all Indonesian people.